Chronic conditions and health literacy in Brazilian community-dwelling older people: a cross-sectional study - Madson Alan Maximiano-Barreto; Ana Caroline Pinto Lima; Daiene de Morais; Élen dos Santos Alves; Bruna Moretti Luchesi (Health Literacy and Communication Open)
Objective: To identify the association between chronic conditions and health literacy in community-dwelling older people in a Brazilian city.Methods Two hundred older people registered at five Family Health Units in the city of Naviraí, Brazil, voluntarily participated in a cross-sectional study. The participants answered a questionnaire addressing sociodemographic characteristics. The participants also answered a health literacy test and were then divided into three groups based on the score: “lower health literacy”, “intermediate health literacy” and “higher health literacy”).Results Men accounted for slightly more than half of the sample (50.5%) and age ranged from 60 to 97 years (X᷈: 69; [IQR: 66–77] years). Individuals with more advanced age (OR: 1.07; 95% CI: 1.02–1.13) and arterial hypertension (OR: 5.56; 95% CI: 2.17–14.21) were more likely to have “lower health literacy”, whereas those with diabetes mellitus (OR: 0.37; 95% CI: 0.16–0.86) were less likely to have “lower health literacy”.Conclusions Low health literacy was associated with the presence of hypertension in older people, but not diabetes mellitus. Further studies on this issue are needed, along with the planning of strategies and public policies to mitigate the negative impacts of low health literacy.